2003
DOI: 10.1074/jbc.m307833200
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of Topological Determinants in Prion Protein (PrP) and Measurement of Transmembrane and Cytosolic PrP during Prion Infection

Abstract: The prion protein (PrP) can adopt multiple membrane topologies, including a fully translocated form ( Sec PrP), two transmembrane forms ( Ntm PrP and Ctm PrP), and a cytosolic form. It is important to understand the factors that influence production of these species, because two of them, Ctm PrP and cytosolic PrP, have been proposed to be key neurotoxic intermediates in certain prion diseases. In this paper, we perform a mutational analysis of PrP synthesized using an in vitro translation system in order to fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 31 publications
2
59
0
Order By: Relevance
“…3A shows that HaPrP(M15) was indeed synthesized by cells based on the presence of a 26-kDa band recognized by ␣PrP 3F4 in the lysates of HaPrP(11C12) and HaPrP(M1S) transfectants. Importantly, the 26-kDa band was also recognized by ␣-SP, an antibody raised against the C-terminal region of the signal sequence (11). In cell lysates, HaPrP(M15) retained the C-terminal hydrophobic segment according to electrophoretic mobility determinations using a panel of recombinant PrP chains consisting of the full unprocessed chain (1-254 sequence), the fully processed chain (23-231 sequence), and N-terminally shortened chains either containing or lacking (15-231) the C-terminal hydrophobic segment (Fig.…”
Section: Haprp(m15) and Huprp(m8) Isoforms Account For De Novo Synthementioning
confidence: 99%
“…3A shows that HaPrP(M15) was indeed synthesized by cells based on the presence of a 26-kDa band recognized by ␣PrP 3F4 in the lysates of HaPrP(11C12) and HaPrP(M1S) transfectants. Importantly, the 26-kDa band was also recognized by ␣-SP, an antibody raised against the C-terminal region of the signal sequence (11). In cell lysates, HaPrP(M15) retained the C-terminal hydrophobic segment according to electrophoretic mobility determinations using a panel of recombinant PrP chains consisting of the full unprocessed chain (1-254 sequence), the fully processed chain (23-231 sequence), and N-terminally shortened chains either containing or lacking (15-231) the C-terminal hydrophobic segment (Fig.…”
Section: Haprp(m15) and Huprp(m8) Isoforms Account For De Novo Synthementioning
confidence: 99%
“…Polyclonal antibody P45-66, raised against a synthetic peptide encompassing residues 45-66 of mouse PrP (25), was used at 1:2,500 for Western blot. An antibody (anti-SP) that selectively recognizes forms of murine PrP containing an uncleaved signal peptide was used at 1:500 for Western blot (26). Anti-giantin (Covance) and anti-trap (Upstate Biotechnologies) antibodies were used, respectively, at 1:1,000 and 1:500 for immunofluorescence staining.…”
Section: Methodsmentioning
confidence: 99%
“…To determine whether L9R-3AV PrP in cerebellar granule neurons also has the same feature, we immunoprecipitated PrP from [ 35 S]methionine-labeled cultures using anti-SP, an antibody that specifically recognizes PrP molecules containing an intact signal peptide (19). Parallel samples were immunoprecipitated with 3F4 or 8H4 antibodies, which recognize PrP molecules regardless of the presence of the signal peptide (see Fig.…”
Section: L9r-3av Prp Retains An Uncleaved Signal Peptide-we Demonstramentioning
confidence: 99%
“…Based on these and other results, it was suggested that Ctm PrP is a key neurotoxic intermediate in both familial and infectious prion diseases and that the amount of this form can be increased directly by pathogenic mutations, or indirectly by accumulation of PrP Sc (8). However, uncertainties remain about the role of Ctm PrP in prion diseases because of recent reports that Ctm PrP levels do not change significantly during scrapie infection (19) or as a result of most pathogenic mutations (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation